Between immunity and impunity: external accountability of political elites for transnational crime - Zabyelina, Yuliya (Cambridge University Press, 2024)
"Examines how state officials and officials of international organizations take advantage of international law immunities to perpetrate transnational crimes and avoid accountability. Focuses on the trafficking in persons and drugs, corruption, and money laundering committed or facilitated by political elites for personal financial or material gain"--